Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/jnci/djr029
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventative Potential of the Cruciferous Vegetable Constituent Phenethyl Isothiocyanate in a Mouse Model of Prostate Cancer

Abstract: In this transgenic model, dietary PEITC suppressed prostate cancer progression by induction of autophagic cell death. Potential biomarkers to assess the response to PEITC treatment in plasma were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
147
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 92 publications
(151 citation statements)
references
References 54 publications
3
147
0
Order By: Relevance
“…12 Further, there was a decreased incidence of PD cancers when TRAMP mice received *15 lmol of phenethyl isothiocyanate per day in their diet. 23 These effective outcomes, compared with the present study, suggest that the effects of a complex mixture of glucosinolates within whole broccoli may be quite different from the effects of pharmacological doses of a pure compound such as I3C.…”
Section: Discussionsupporting
confidence: 44%
See 2 more Smart Citations
“…12 Further, there was a decreased incidence of PD cancers when TRAMP mice received *15 lmol of phenethyl isothiocyanate per day in their diet. 23 These effective outcomes, compared with the present study, suggest that the effects of a complex mixture of glucosinolates within whole broccoli may be quite different from the effects of pharmacological doses of a pure compound such as I3C.…”
Section: Discussionsupporting
confidence: 44%
“…For example, a diet containing 1% I3C significantly reduced genitourinary tract weight 11 and TRAMP mice gavaged with 3 lmol of DIM had an increased incidence of PIN and a decreased incidence of WD carcinoma, indicating a slowing of prostate cancer progression. 13 Additionally several other studies that treated TRAMP mice with individual phytochemicals found in broccoli or broccoli sprouts have also observed reductions in prostate carcinogenesis 12,23,24 (Table 5 and personal communication with Dr. Emily Ho, Oregon State University, Corvallis, OR, USA, April 16, 2011). Reduction in the incidence of PIN and WD carcinomas was observed when TRAMP mice were gavaged with 6 lmol sulforaphane every other day.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…25 The cancer-protective effects of cruciferous vegetables likely involve complex interactions of multiple mechanisms, and most research to date has focused on the capacity of cruciferous vegetable ingredients to alter biotransformation enzyme expression and activities. Isothiocyanates, a constituent of cruciferous vegetables, have been hypothesized to reduce the risk of prostate cancer through induction of phase I and phase II 26 suggesting that cruciferous vegetables are most important in the early stages of prostate cancer. Interestingly, the inverse association seems to be stronger for advanced stages of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, isothiocyanates, including phenethyl isothiocyanate and sulforaphane, have also been shown to inhibit prostate cancer cell growth and induction of apoptosis in vitro and in vivo by repression of androgen receptor and induction of endogenous cyclin-dependent kinase. [26][27][28][29][30][31] In addition, other chemicals derived from cruciferous vegetables, such as 3,3′-diindolylmethane, have been shown to act similarly on prostate cancer. 32,33 The present study had important limitations.…”
Section: Discussionmentioning
confidence: 99%